Comparative Evaluation On Number Of Increments Of Composites Used For Restoring Mesio - Occlusal Cavities Of Maxillary And Mandibular Molars - A Retrospective Study - S.K, SWARNA.; S, PRADEEP; S, HARIPRIYA (The journal of contemporary issues in business and government, 2021)
Dental composites are generally composed of matrix monomers such as Bis-GMA and UDMA and silica is commonly used as filler. Modifying the composition and size of filler particles, have improved wear resistance of composites. With advances in adhesives and bonding strategies, the interface of tooth-restoration is improvised but still microleakage due to polymerization shrinkage stresses is a major drawback of composite resin restorations. Incremental layering technique of placing composite restorations greatly reduced the shrinkage stresses. This study was done to evaluate the number of increments of composite used for restoring mesio- occlusal cavities of maxillary and mandibular molars in the South Indian population. A total of 142 case sheets of patients who underwent class II mesio – occlusal composite restorations in maxillary and mandibular molars were reviewed, analyzed and comparatively evaluated. The statistical analysis was done using SPSS software (Version 23). In our study, the patients selected were in the age group of 18- 65 years. Class 2 composite restorations were mostly done in the age group of 31- 40 years followed by 18-30 years respectively. In the selected cases, 74 (52.1%) were male and 68 (47.8%) were female patients. Maxillary right first and second molars were the most commonly treated teeth. Out of 142 teeth, 39 teeth (27.4%) used 1 increment, 81 teeth (57%) used 2 increments and 22 teeth (15.4 %) used 3 increments of composite for restoration of class II cavities.Two increments of composites were used in most cases of mesio-occlusal cavities of all posterior teeth. The association between age, gender and number of composite increments did not have any statistically significant difference in maxillary and mandibular class II cavities (p > 0.05). From this study we observed that all the teeth were restored in a conservative approach.